Malnutrition and Childhood Illness among 1–5-year-old Children in an Urban Slum in Faridabad: A Cross-Sectional Study - Pooja Goyal; Shveta Lukhmana; Shivam Dixit; Abhishek Singh (Journal of Epidemiology and Global Health, 2019)
A community-based, cross-sectional study was conducted among 202 children aged 1–5 years residing in an urban slum to study the extent of malnutrition and its association with common childhood illness(es). The participants were selected using convenient sampling (nonprobability), and the appropriate respondents were interviewed using a structured, semi-openended, pretested, interviewer-administered questionnaire. The prevalence of undernutrition (weight for age), stunting (height for age), and wasting (weight for height) were calculated at the cutoff level of =2 standard deviation (Z-score <-2) of the National Centre for Health Statistics (NCHS) reference median values. Data were analyzed using appropriate tests of significance. The mean age of participants was 33.9 ± 13.9 months. The proportion of undernutrition, stunting, and wasting among was found to be 29.2%, 66.8%, and 12.9%, respectively. Respiratory illness (56.9%) was reportedly the most common morbidity among participants. A higher proportion of children who reportedly suffered from viral fever in past 3 months were wasted, and this association was found to be statistically significant (p = 0.003). The alarming rate of malnutrition reiterates the synergistic relationship between common infections and malnutrition. It is, therefore, imperative to emphasize and strengthen the role of nutritional interventions as outlined by the World Health Organization (WHO) Integrated Management of Childhood Illness as part of case management for infectious diseases among children aged <5 years.